CD4+/CD8+ ratio of liver-derived lymphocytes is related to viraemia and not to hepatitis C virus genotypes in chronic hepatitis C. - Pham, B N (1995)
The pathogenic mechanisms that lead to chronic hepatitis C are unknown. As hepatitis C virus (HCV) has been shown to induce T cell response, we assessed whether a particular T lymphocyte subset could be preferentially detected in the liver of patients with chronic hepatitis C in relation to viraemia or HCV genotypes. The immunophenotypes of liver-derived lymphocytes were analysed in 26 patients by flow cytometry and immunohistochemistry. Viraemia was quantified by branched DNA assay. Using this assay, HCV RNA was not detectable in six patients. HCV RNA was detected in 20 patients, and titres ranged from 8 to 137 x 10(6) Eq/ml. Genotyping was performed using a line probe assay. Type 1a, 1b, 2a, 3a and 4a were found to infect 2, 10, 2, 7 and 3 patients, respectively. The CD4+/CD8+ ratio of liver-derived lymphocytes was significantly higher (P < 0.01) in patients with detectable viraemia than in patients without detectable viraemia. In contrast, neither the percentage of gamma/delta T lymphocytes nor that of CD2+CD57+ cells was different in the groups. When comparing the CD4+/CD8+ ratio, the percentage of gamma/delta T lymphocytes or CD2+CD57+ cells according to genotype, the differences were not significant. These results suggest that the CD4+/CD8+ ratio of liver-derived lymphocytes is related to viraemia but not to HCV genotypes in patients with chronic hepatitis C, and that T lymphocytes may be involved in the pathogenesis of liver lesions in chronic hepatitis C.